Experimental testing of pre-stressed timber-to-timber composite (TTC) floors. (15th December 2019) - Giongo, Ivan; Schiro, Gianni; Walsh, Kevin; Riccadonna, Daniele
Highlights: Experimental out-of-plane testing of pre-stressed TTC floor specimens is reported. The applicability of a pre-stressing procedure based solely on the use of screws is proof-tested. Hybrid (softwood/hardwood, CLT/GLT/LVL) timber-to-timber solutions are investigated. Experimental data are compared with designs from codes and theoretic formulations. Abstract: The experimental out-of-plane performance of timber-to-timber composite floor structures was experimentally investigated. Specifically, 6-point bending tests were performed on seventeen full-scale floor specimens (6.4 m span) assembled with inclined screw fasteners (both single threaded and double threaded screws) and by using combinations of different timber products (e.g. spruce cross laminated panels, beech laminated veneer lumber beams/panels). For most of the specimens, a cambering and pre-stressing technique (CP procedure) was utilised by exploiting the compression force produced by screw fasteners. The experimental observations indicated that it is possible to obtain camber values that go from approximately 1/900 to 1/250 of the floor span, according to the design needs. As an indicator of the wide possible range of pre-stress forces, the vertical force required to eliminate the camber was monitored during testing, resulting in measured values ranging from 2.4 kN/m 2 to 13.8 kN/m 2 (0.6 m joist spacing). The applicability of the proposed solutions in real design scenarios was evaluated by comparing the experimental results with the predictions obtained by using a proposed analytical approach. A good correlation was observed between the test data and the theoretical predictions.